Förändras mjölkens proteinsammansättning i separata juverdelar i samband med höga celltal (SCC)? - Åkerstedt, Maria (2007)
Today the milk production per cow is increasing but the milk delivered by the Swedish farmer contains less amounts of fat and protein than earlier. The contents have decreased since 1993. In average the milk contain 4,2 percent fat and 3,4 percent protein. Earlier the fat content in milk was important. Nowadays the dairy's attention has turned to the milk's valuable proteins, principally the caseins, which have a considerable nutritional value and are important for several dairy products like cheese and yoghurt.